Development of Novel Diclofenac Analogs Designed to Avoid Metabolic Activation and Hepatocyte Toxicity - Tateishi, Yasuhiro (ACS Omega, 2020)
[Image: see text] Diclofenac (DCF) is widely used as a nonsteroidal anti-inflammatory drug; however, it is associated with severe liver injury. This adverse reaction is thought to be related to the reactive quinone imine (QI) and acyl glucuronide (AG) metabolites of DCF, but it remains controversial which reactive metabolites mainly contribute to DCF-induced toxicity. In this study, we synthesized five types of DCF analogs that were designed to mitigate the formation of reactive QI and/or AG metabolites and evaluated their metabolic stability, cyclooxygenase (COX) inhibitory activity, and toxicity to cryopreserved human hepatocytes. Compounds with fluorine at the 5- and 4′-positions of aromatic rings exhibited modest and high metabolic stability to oxidation by cytochrome P450, respectively, but induced cytotoxicity comparable to DCF. Replacing the carboxylic group of DCF with its bioisosteres was effective in terms of stability to oxidative metabolism and glucuronidation; however, sulfonic acid and sulfonamide groups were not preferable for COX inhibition, and tetrazole-containing analogs induced strong cytotoxicity. On the other hand, compounds that have fluorine at the benzylic position were resistant to glucuronidation and showed little toxicity to hepatocytes. In addition, among these compounds, those with hydrogen at the 4′-position (2a and 2c) selectively inhibited the COX-2 enzyme. Throughout these data, it was suggested that compounds 2a and 2c might be novel safer and more efficacious drug candidates instead of DCF.